DESIGN AND ANALYSIS OF SAFETY SIDE STAND FOR MOTORCYCLE - Mr. S. B. Masuti; Mr. M. B. Mane; Mr. V.V. Korshetti; Mr. K. A. Ghurghure (International Engineering Journal For Research & Development, 2022)
Life in twenty first century is very fast and sometimes unknowingly the rider starts the bike and move forward without pulling off the side stand because of urgency which may cause unavoidable accidents. To avoid such accidents cause due to the carelessness of rider, we may produce the new advancement in bike that as we press the gear lever, the cable wire get stretched due to the hook catch lock get delocked to lift the side stand automatically. There is a need of prevent the rider in this type of condition, which arises many times, hence, it is important to create one mechanism, which prevents the rider from the accidents caused due to ungifted side stand. The mechanism should be such that it should neither affect the original mechanism nor create make the side stand more bulky. In additional it should not increase the price of the bike. It is just a small mechanism, which operate the stand and operation will be easy. Therefore, it is necessary to have a separate attachment in a bike to lift up the side stand automatically. The safety side stand relates to the side stand for general motorcycle. It is characterized by means to rigid the stand, in inclined area. When the motorbike is in the respite on a ramp, the typical stand would reverse, where as in safety stand the inverse action is locked, and simultaneously all the means for the movement of the bike is sealed by a trifling mechanism that works mechanically. The prototype was generated and analyzed using the Dassault System CatiaV5 software.